India-China relations politics of resources, identity and authority in a multipolar world order - Panda, Jagannath P. (Routledge advances in South Asian studies, 2017)
The driving theme of this book is to highlight the enduring and emerging complexities in India-China relations, which are multi-layered and polygonal in nature, and both a result and reflection of a multipolar world order. The book argues that coexistence between India and China in this multipolar world order is possible, but that it is limited to a medium-term perspective, given the constraints of identity complexities and global aspirations these two rising powers are pursuing. It goes on to discuss how their search for energy resources, quest to uphold their own identity as developing powers, and engagement in balance-of-power politics to exert authority on each other's presence, are some elements that guide their non-cooperative relationship.